PERBEDAAN KOMPRES AIR HANGAT DAN JAHE MERAH TERHADAP TINGKAT NYERI GOUT LANSIA - Rita Merliana; Novita Elisabeth Daeli; Morlina Sitanggang (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
Increased uric acid levels in the blood (hyperuricemia)is cause by buildup of uric acid levels and its knowas a gout illness. Decreasing of kidney function such as disability, inflammation, swelling, redness and painthat disrupts daily activities are some of the effects caused by gout. Gout pain can be handledbypharmacological and non-pharmacological therapy. The example of Non-pharmacological therapy likewarm water compress therapy and red onion compress (zingiber officinale var rubrum).To determine thedifferences of warm water compresses and red onion compress (zingiber officinale var rubrum) of goutpain level in the elderly at the Palembang Nursing Home. This study used a quantitative study, with aquasi-experimental design method by pretest posttest design, sampling used a total sampling of 42respondents. Bivariate analysis using the Wilcoxon and Mann-Whitney tests.The characteristic of allrespondents are aged 60-74 years (100%), the majority of female sex (66.7%), uric acid levels> 7.1 mg / dL(61.9%), the level of pain pretest (7- 9) (59.5%), posttest (1-3) (66.7%), type of gout therapy: warm watercompress (50%), red onion compress (50%). Wilcoxon test results show that warm water compresses with pvalue: 0.00 and red onion compresses with p value: 0.00, its mean that there are differences before andafter the intervention given to the extent of gout pain. Mann-Whitney test with p value 0.518 indicates thatthere is no difference in warm water compresses and red onion compress with mean rank of red onioncompress is 20.50 and mean rank of warm water compresses is 22.50.Warm water compress and red onioncompress together can reduce pain but red onion compress are more effective. This research is expected tobe a reference for using red onion compress (zingiber officinale var rubrum) as a one non-pharmacologicaltherapy to treat gout pain in the elderly.